Yüksek Sıcaklığın Beton Üzerindeki Etkileri - Uysal, Alper (Fen Bilimleri Enstitüsü, 2015)
Yapılan bu çalışmada çeşitli betonarme yapı elemanları için ısı iletimi durumları incelenmiştir. Öncelikle ele alınan yapı elemanları matematiksel olarak modellenmiştir. Daha sonra uygun sınır koşulları için özel çözümler elde edilmiştir. Hesaplar için perde, kolon, döşeme ve kiriş betonarme elemanlar kullanılmıştır. Perde elemanların iki yüzeyinden, kolon elemanların da dört yüzeyinden yüksek sıcaklık etkisine maruz kaldığı düşünülmüştür. Yine döşeme elemanlar için y1>y2 olmak üzere; alt yüzeyinden y1 ve üst yüzeyinden y2 sıcaklık değerinin tesir ettiği durumlar için çözümler yapılmıştır. Kiriş elemanlarda ise etkinin üç yüzeyden de tesir ettiği düşünülmüştür. Kullanılmak istenen beton cinsine göre; ısı iletimi katsayısı (k), özgül yoğunluk (), özgül ısı (c) ve ısısal yayınım katsayıları () kullanılarak değişik yüksek sıcaklık değerleri için (0C) sonuçlar elde edilmiştir. Bulunan bu sonuçlar grafik tabloları haline getirilerek yapı elemanları içersindeki sıcaklık dağılımları incelenmiştir. Yapılan bu incelemeler sonucunda betonarme yapı elemanlarındaki boyut artışının ve fiziksel özelliklerin iyileştirilmesinin yangın dayanımı üzerindeki olumlu etkileri açıklanmıştır.

In this study, the cases of heat transfer for various reinforced concrete construction materials have been investigated. First of all, the construction materials discussed have mathematically been modeled. Next, specific solutions for appropriate boundary conditions have been obtained. For the calculations, reinforced concrete construction materials such as sheetwall, column and slab have been employed. The sheetwall and column elements were presumed to have been exposed to the impact of high temperature from their two surfaces and four surfaces respectively. Again for the slab elements, taking y1 > y2; special solutions for the cases, where the temperature value of y1 is imposed from the lower surface and y2 from the upper surface, have been developed. As to the beam elements, such impact was presumed to have been imposed from all the three surfaces. oC results have been obtained for various high temperature values, using the relevant heat transfer coefficient (k), specific density (p), specific heat (c) and heat diffusion coefficients () depending on the given type of concrete. The results derived have been compiled and transformed into graphical tables and temperature distributions in the construction materials have been studied. As a consequence of such studies, the positive effects of the elongation of reinforced concrete construction materials and the improvement of their physical properties on fire resistance have been described.
Impacts Of High Temperature On Concrete
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2004
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2004
Keywords: yüksek sıcaklık; ısı iletimi; beton; yangın dayanımı; sıcaklık dağılımı; high temperature; heat transfer; concrete; fire resistance; temperature distribution